1992
DOI: 10.1002/etc.5620111205
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics in aquatic systems: Model comparisons and use in hazard assessment

Abstract: -Toxicokinetic models are not constrained by assumptions of equilibrium as are thermodynamic (equilibrium-partitioning) models and are more accurate predictors of toxicant accumulation for non-steady-state exposures and multiple uptake routes. Toxicokinetic models -compartmentbased models, physiological-based models, and energetics-based models-are reviewed and the different mathematical formalisms compared. Additionally, the residue-based toxicity approach is reviewed. Coupling toxicokinetic models with tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
250
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(253 citation statements)
references
References 123 publications
2
250
0
1
Order By: Relevance
“…First order growth rate constants, as applied in some models to account for biomass increases (see Landrum et al, 1992) have therefore not been applied. An overview of the parameters used is provided in Table 1.…”
Section: Sea Watermentioning
confidence: 99%
“…First order growth rate constants, as applied in some models to account for biomass increases (see Landrum et al, 1992) have therefore not been applied. An overview of the parameters used is provided in Table 1.…”
Section: Sea Watermentioning
confidence: 99%
“…The present study examines Cu-Cd interactions in mature tilapia, paying particular attention to organs with diverse biological functions, because it is anticipated that differences in metal accumulation between organs will be related to their functions. Organ metal concentration or metalmetal interaction at this level may be a link to toxicity (Foulkes, 1990;Landrum et al, 1992). In keeping with this, it has recently been suggested that metal concentrations in the organs of fish, rather than the metal concentrations in the ambient water, could be used as a biomonitor for water pollution in natural freshwaters (Handy, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability of brominated flame retardants in sediment Environ Toxicol Chem 32, 2013growth dilution, and sediment concentration remaining constant throughout the testing [24,25] …”
Section: Discussionmentioning
confidence: 99%